2001
DOI: 10.1074/jbc.m102524200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Macrophage Matrix Metalloproteinase Biosynthesis by Surfactant Protein D

Abstract: Recent studies strongly suggest that surfactant protein D (SP-D) plays important roles in pulmonary host defense and the regulation of immune and inflammatory reactions in the lung. Although SP-D can bind to alveolar macrophages and can elicit their chemotaxis, relatively little is known about the direct cellular consequences of SP-D on the function of these cells. Because matrix metalloproteinases (MMPs) are synthesized in increased amounts in response to various proinflammatory stimuli, we investigated the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 61 publications
1
2
0
1
Order By: Relevance
“…We also observed significantly higher SP-D concentrations in these exposed rock drillers as previously reported (Ellingsen et al 2022 ), SP-D has been shown to induce MMP-12 in human macrophages (Trask et al 2001 ). Associations between SP-D and MMP-12 have hardly been studied and should be addressed in future studies.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed significantly higher SP-D concentrations in these exposed rock drillers as previously reported (Ellingsen et al 2022 ), SP-D has been shown to induce MMP-12 in human macrophages (Trask et al 2001 ). Associations between SP-D and MMP-12 have hardly been studied and should be addressed in future studies.…”
Section: Discussionsupporting
confidence: 90%
“…Antioxidants N-acetylcysteine and pyrrolidine dithiocarbamate inhibited MMP production by AMs from SP-D(-/-) mice (44). Trask et al, 2001, reported that recombinant rat SP-D dodecamers selectively induce the biosynthesis of collagenase-1 (MMP-1), stromelysin (MMP-3), and macrophage elastase (MMP-12) without significantly increasing the production of tumor necrosis factor alpha and interleukin-1beta (45). SP-D did not alter the production of these MMPs by fibroblasts.…”
Section: Sp-a Sp-d and Matrix-metalloproteinasesmentioning
confidence: 97%
“…This seems counterintuitive, as an antifibrotic mediator is upregulated lung parenchyma, yet the lungs in IPF, by definition, become fibrotic. This can be explained by the preferential expression of MMP1 in different lung tissue: MMP1 overexpression is localized to the alveolar epithelial cells (AEC) and lung macrophages, allowing fibrosis elsewhere in the interstitial lung compartment [29][30][31][32]. Furthermore, MMP3 is believed to be involved in the pathogenesis of IPF by inducing epithelial to mesenchymal transition.…”
Section: Mmps In Pulmonary Fibrosismentioning
confidence: 99%